Pemberdayaan Sumber Daya Alam di Bidang Perikanan sebagai Mata Pencaharian Masyarakat Kelurahan Petuk Katimpun: Empowerment of Natural Resources in the Fisheries Sector as a Livelihood for the Community of Petuk Katimpun Village - Kristina, Parista; Saputra, Erik; Marbun, Ronauli; Situmeang, Mauliwati; Ucok, Ucok; Sianturi, Hutri; Hutauruk, Ramces; Tinambunan, Torang; Purba, Waldensius; Sinurat, Ditya Sriwahyuni; Siagian, Natanael; Mulyadi, Aditya Rahmat; Marbun, Wawan Mastiar; Lumbantoruan, Eko Haryanto; Rahayuningsih, Sri Endang Agustina (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2024)
Petuk Katimpun Village, located in Palangka Raya City, has natural fisheries resources that have yet to be utilized optimally. This is due to the need for more public knowledge about managing fisheries resources, especially the diversification of fish processing which can be used as a livelihood for the community. Therefore, empowerment efforts are needed through outreach, training, and monitoring, focusing on processing fishery products into food products, such as fish jerky. This community service activity aims to provide understanding and skills to the people of Petuk Katimpun Village in managing fisheries resources, focusing on making fish jerky as an economical product. Methodology for community empowerment services carried out in Petuk Katimpun Village, Jekan Raya District, Palangka Raya City, Central Kalimantan Province. The community empowerment service will be carried out from July to November 2023. The activity implementation is socialization, training, and monitoring in making food products in the form of fish jerky. Participants in the activity are housewives and fishermen. The duration of this community empowerment service activity lasts for five months. Based on the results of the training evaluation, it is known that the community's knowledge about fish jerky processing before and after the training has dramatically increased by 66.12%.